Nutritional Properties, Antioxidant and Enzyme Inhibitory Activities of Bread Sweetened with Date Fruit - Albert Akinsola Famuwagun; Saka Olasunkanmi Gbadamosi (Turkish Journal of Agriculture: Food Science and Technology)
The study investigated the potentials of date fruit as sweetening agent in bread and determined micronutrient composition, antioxidant properties and inhibition of diabetic related enzymes such as the alpha amylase and glucosidase. The fibre and ash contents of the samples increased with the addition of date fruit. The phosphorous, calcium, potassium, iron and magnesium contents of the bread sweetened with date fruit pulp were higher when compared to the bread samples that contained granulated sugar. Bread samples that contained date fruit exhibited greater DPPH radical scavenging activities, metal chelating activities, FRAP and possessed higher inhibition against α-amylase and glucosidase when compared with bead that contained granulated sugar. The results also showed greater antioxidant and enzyme inhibitory activities in the bread sweetened with dry date fruits that the wet date fruits. The sensory results showed that bread sweetened with granulated sugar and the date fruits were not significantly different from one another. The overall results showed date fruit has dual potentials in bread, as sweetener and as ingredient in enhancing nutritional qualities of bread.